Syntheses, Electrochemical, Linear Optical, and Cubic Nonlinear Optical Properties of Ruthenium–Alkynyl‐Functionalized Oligo(phenylenevinylene) Stars1. Issue 8 (3rd July 2015) - Chen, Zhiwei; Jeffery, Christopher J.; Morshedi, Mahbod; Moxey, Graeme J.; Barlow, Adam; Yang, Xinwei; Babgi, Bandar A.; Dalton, Gulliver T.; Randles, Michael D.; Smith, Matthew K.; Zhang, Chi; Samoc, Marek; et al.
Abstract: The syntheses of trans ‐[Ru(C≡CC6 H4 ‐4‐CHO)(C≡CC6 H4 ‐4‐R)(dppe)2 ] (R=H (9 a ), NO2 (9 b ), CHO (9 c ), C≡CC6 H3 ‐3, 5‐Et2 (9 d ), ( E )‐CHCHC6 H4 ‐4‐ t Bu (9 e ); dppe=1, 2‐bis(diphenylphosphino)ethane), trans ‐[Ru(C≡CC6 H4 ‐4‐R)Cl(dppe)2 ] (R=C≡CC6 H3 ‐3, 5‐Et2 (11 a ), ( E )‐CHCHC6 H4 ‐4‐ t Bu (11 b ), ( E )‐CHCHC6 H4 ‐4‐NO2 (11 c )), 1, 2, 4, 5‐ trans ‐[(dppe)2 (RC6 H4 C≡C)RuC≡CC6 H4 ‐4‐( E )‐CHCH]4 C6 H2 (R=H (14 a ), C≡CC6 H3 ‐3, 5‐Et2 (14 b ), ( E )‐CHCHC6 H4 ‐4‐ t Bu (14 c )), 1‐I‐3, 5‐ trans ‐[(L2 )2 (R)RuC≡CC6 H4 ‐4‐( E )‐CHCH]2 C6 H3 (L2 =1, 1‐bis(diphenylphosphino)methane (dppm)), R=Cl (15 a ); L2 =dppe, R=C≡CPh (15 b ), R=C≡CC6 H4 ‐4‐NO2 (15 c )), 1‐Me3 SiC≡C‐3, 5‐ trans ‐[(L2 )2 (R)RuC≡CC6 H4 ‐4‐( E )‐CHCH]2 C6 H3 (L2 =dppm, R=Cl (16 a ); L2 =dppe, R=C≡CPh (16 b )), 1‐HC≡C‐3, 5‐ trans ‐[(dppe)2 (R)RuC≡CC6 H4 ‐4‐( E )‐CHCH]2 C6 H3 (R=Cl (17 a ), R=C≡CPh (17 b )), and 1, 3, 5‐ trans ‐[(dppe)2 (3, 5‐R2 ‐C6 H3 C≡C)RuC≡CC6 H4 ‐4‐( E )‐CHCH]3 C6 H3 (R=( E )‐CHCHC6 H4 ‐4‐C≡C‐ trans ‐[Ru(C≡CPh)(dppe)2 ] (18 )) are reported together with those of the precursor alkynes 1‐RC≡C‐3, 5‐Et2 C6 H3 (R=SiMe3 (2 ), H (3 ), C6 H4 ‐4‐C≡CSiMe3 (5 ), C6 H4 ‐4‐C≡CH (6 )). The identities of9 c, 9 d, 9 e, 11 a, and trans ‐[RuC≡CC6 H4 ‐4‐( E )‐CHCHC6 H4 ‐4‐ t Bu2 (dppe)2 ] (12 and12′ ) were confirmed by single‐crystal X‐ray diffraction studies. The electrochemical properties of9 a –e, 11 a –b, 14 a –c, 15 a –c, 16 b, 17 a, 17 b, and18 were assessed by cyclic voltammetry; the studies reveal that potentials for the fully/quasi‐reversible metal‐centered oxidation processes decrease upon introduction of solubilizing alkyl substituents and increase upon increasing acceptor substituent strength; other structural variations have little impact. UV/Vis‐NIR spectroscopic studies on these complexes reveal lowest‐energy metal–ligand charge transfer (MLCT) bands that redshift upon increasing the acceptor substituent strength, blueshift on alkyl incorporation, and gain in intensity on progression from linear to star complexes. Low‐temperature UV/Vis‐NIR spectroelectrochemical studies of14 a –c show the appearance of an intense low‐energy band at 7400–7900 cm −1 that is redshifted upon π‐system lengthening and alkyl substituent incorporation. The cubic nonlinear optical properties of9 d, 9 e, 14 a –c, 15 a –c, 16 b, 17 a, b, and18 were assayed by femtosecond Z‐scan studies at benchmark wavelengths (750 and 800 nm) in the near‐IR region, with nonlinearity increasing upon nitro incorporation; the values for the E ‐ene‐linked dendrimers in these studies are much larger than yne‐linked analogues. Compounds9 d, 9 e, 14 a –c, and18 were further examined by broad‐spectral‐range femtosecond Z‐scan studies; the cruciform complexes have appreciable multiphoton absorption cross‐sections, with maximal values close to two and three times the wavelength of the linear optical absorption maxima. Abstract : Super stars : (4‐Formylphenylethynyl)ruthenium complexes (see figure) are shown to undergo "chemistry‐on‐complex" Horner–Wadsworth–Emmons coupling to afford a range of tri‐ and tetraruthenium‐functionalized star molecules and a nonaruthenium dendrimer. The products are nonlinear optical (NLO)‐active, with linear optical properties that are redox‐switchable.